Active Learning Metamodels for Transport Simulation Problems - Antunes, Francisco José Nibau (2021)
Thesis developed within the Doctoral Program in Transport Systems, supervised by Professors Bernardete Ribeiro and Francisco Pereira, and presented to the Department of Civil Engineering of the Faculty of Sciences and Technology of the University of Coimbra.